Defect-mediated runaway oxidation of electroplated tin - Fabro, Marie Angelynne C.
Pure tin is widely used as a replacement of Pb-Sn eutectic alloy as finish and solder material. The normal oxide film is thin, passivating, and grows logarithmically with time. The tendency to form an undesired thick oxide layer under high temperature conditions is documented, but poorly understood. This study aims to determine the mechanism of runaway oxidation of pure tin electroplated coatings. Pure tin was electroplated on an aluminum substrate in a Hull cell at a total current of 3 A at an average temperature of 47°C. Plating was performed in agitated electrolyte baths of simultaneously increasing organic additives concentrations. The primary additive concentration ranged from the normal level of 100 mL/L to 600 mL/L. The secondary additive concentration ranged from the normal level of 8 mL/L to 48 mL/L. Current densities of 15, 8 and 3 A/dm2 were considered. The oxide was grown on the electroplated tin through a) 24-hour bake at 100°C, b) 48-hr bake at 85°C and 85% relative humidity, and c) 48-hr bake at 85°C and 85% relative humidity followed by two passes of reflow at 260°C. The thickest oxide layer was formed on samples that were subjected to reflow. XRD patterns confirm the presence of SnO2 and preferred planes. Thickness of the oxide layers were estimated using color analysis and secondary ion mass spectrometry depth profiling. The increased concentration of organic plating additives from normal to six times the normal levels used during the electrodeposition of pure tin caused an increase in carbon content of the deposit. Mott-Schottky measurements showed increasing electron donor density of up to four orders of magnitude as a function of current density and carbon content. A higher current density during deposition causes the tin oxide film to reach the donor density saturation value at lower concentrations of organic plating additives. This change in the electron donor density increases the number of electrons that migrate to the oxide-gas interface, thus increasing the amount of oxide anion formed. The chemisorbed oxide anions draw electrons from the oxide layer, creating a potential difference between the metal-oxide interface and the oxide-gas interface. The oxygen migrates through the oxide layer to the metal-oxide interface, thus increasing the thickness of the oxide layer. The rate of oxide layer growth is thus due to Fickian diffusion, and diffusion under an electric fi